Evaluasi Program Literasi dan Numerasi Rutin Dalam Peningkatan Minat Belajar Pada Siswa Di SD Negeri 2 Dawan Klod - Priatna, Yolan; Kade Septiari, Ida Ayu (Education Library, 2026)
This research aims to evaluate the routine literacy and numeracy program at SD Negeri 2 Dawan Klod in increasing students' interest in learning. This program is one of the main strategies implemented to overcome low student involvement in the learning process. The research uses a qualitative approach with primary data obtained through interviews and observations, as well as secondary data from school documents. The research results show that this program has a positive impact on students' interest in learning through the application of various strategies, such as directed reading, integration of numeracy in real life, collaborative learning, and the use of interactive learning media. However, obstacles such as limited facilities, short lesson time, and variations in teaching materials are still the main challenges. To increase the effectiveness of the program, development of learning facilities, teacher training, and cooperation between schools and parents are needed. In conclusion, routine literacy and numeracy programs have great potential in increasing students' interest in learning, but require continuous evaluation and improvement for more optimal results.